Regulatory thresholds of household deposit stability in the euro area - neglected factors and omissions made - Kochaniak Katarzyna (Panoeconomicus, 2019)
The paper investigates the occurrence of three categories of household deposits in 15 euro area countries - guaranteed, high value, and very high value - which, according to the European Banking Authority, differ in terms of their sensitivity to outflows under stress. The analysis is based on household-level data and applies a logit model. Its main finding is that the impact of wealth and socio-demographic features of households on their propensity to possess the deposits was opposite regarding guaranteed and unguaranteed deposits. It proves two separate profiles of households who declared deposits in the euro area. For selected member states, the adoption of the single limit within guarantee schemes was assessed as an incentive which may strengthen the deposits’ resilience on withdrawals, and thus positively influence the funding stability of credit institutions.